Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos María Eugenia Durán y centro educativo Canadiense de la ciudad de Santo Domingo, provincia de Santo Domingo de los Tsáchilas en el año lectivo 2012-2013 - Saldaña Rodriguez, Maria Leidiana (2013)
This research, whose purpose was to determine the educational management and school social climate of the classroom, from the perception of students and teachers in the School "Clemencia Rodriguez de Mora" in the urban area, and the School "Cesar Augusto Guamán Cando" in the rural area results that will be a valuable contribution to optimize educational processes in both institutions. In practice such methods were used: analytic-synthetic, inductive-deductive, statistical, and hermeneutic and technical tools: observation sheets, and Trickett Moss questionnaires, interviews and surveys of teachers and students in the 7th year basic general, obtaining data sequentially tabulated quantitatively and qualitatively, allowing us to get to the analysis: comparative critical and reflective of our educational reality. We can not see sideways problems such as lack of cooperation and teacher-student communication, classroom indiscipline, poor academic performance, lack of motivation, lack of interest in the subjects, nullity of tics, routine, improvisation, etc.. With this background, is displayed below the report, a proposed solution to one of the greatest care problems in the institutions investigated, with the aim of contributing to the improvement of educational quality.